Oxidative stress promotes proliferation and dedifferentiation of retina glial cells in vitro - Abrahan, Carolina Elizabeth (2009)
Oxidative damage is involved in triggering neuronal death in several retinal neurodegenerative diseases. the recent finding of stem cells in the retina suggests that both preventing neuronal death and replacing lost neurons might be useful strategies for treating these diseases. we have previously shown that oxidative stress induces apoptosis in cultured retinal neurons. we now investigated the response of müller cells, proposed as retina stem cells, to this damage. treatment of glial cell cultures prepared from rat retinas with the oxidant paraquat (pq) did not induce glial cell apoptosis. instead, pq promoted their rapid dedifferentiation and proliferation. pq decreased expression of a marker of differentiated glial cells, simultaneously increasing the expression of smooth muscle actin, shown to increase with glial dedifferentiation, the levels of cell‐cycle markers, and the number of glial cells in the cultures. in addition, glial cells protected neurons in coculture from apoptosis induced by pq and h2o2. in pure neuronal cultures, pq induced apoptosis of photoreceptors and amacrine neurons, simultaneously decreasing the percentage of neurons preserving mitochondrial membrane potential; coculturing neurons with glial cells completely prevented pq‐induced apoptosis and preserved mitochondrial potential in both neuronal types. these results demonstrate that oxidative damage activated different responses in müller glial cells; they rapidly dedifferentiated and enhanced their proliferation, concurrently preventing neuronal apoptosis. glial cells might not only preserve neuronal survival but also activate their cell cycle in order to provide a pool of new progenitor cells that might eventually be manipulated to preserve retinal functionality.